Pengaruh Kapabilitas Kepemimpinan, Kompetensi Dosen dan Komitmen Dosen Terhadap Akuntabilitas Lembaga Penjaminan Mutu Serta Dampaknya Terhadap Kinerja Uin Maulanan Malik Ibrahim Malang - Ahmad Qurtubi (Journal on Education, 2021)
This research aims to investigate the impact of leadership capability on UIN Maulana Malik Ibrahim Malang performance as conveyed through lecturer competence, lecturer commitment, and institutional accountability. The number of respondents who participated in this research was 188. All respondents are lecturers at UIN Maulana Malik Ibrahim Malang. This research uses a quantitative approach. The data used in this research are primary data obtained from the results of completed questionnaires. The analytical technique used in this research was SEM-PLS analysis performed using the SmartPLS program. Based on the results of the analysis of this research, it was concluded that the leadership capability of UIN Maulana Malik Ibrahim Malang supervisor has a significant impact on institutional performance directly or indirectly through lecturer competence, lecturer commitment, and institutional accountability. Good leadership certainly fosters lecturer competence, lecturer commitment, and institutional responsibility, which will then support higher tertiary performance.